Spectrally-resolved absorption cross-section measurements of shock-heated O2 for the development of a vibrational temperature diagnostic. (August 2021) - Krish, Ajay; Streicher, Jesse W.; Hanson, Ronald K.
Abstract: In shock-heated high-enthalpy air flows, the vibrational temperature of oxygen ( O 2 ) provides critical insight into the non-equilibrium chemistry. Here, a two-color O 2 vibrational temperature diagnostic was developed by utilizing spectroscopic models to inform optimal wavelength candidates for both a continuous-wave (CW), ultraviolet (UV) laser and a picosecond pulsed, UV laser. Cross-sections of shock-heated O 2 were measured using a CW UV laser, and results over a range of wavelengths and temperatures are compared against a Stanford model and Specair, a spectroscopic model for high temperature air species developed by Laux et al. All measurements were completed behind reflected shocks in 2% and 5% O 2 in argon (Ar) mixtures. Vibrational temperatures for cross-section measurements were calculated for plateaus and peaks in experimental absorbances using a Bethe-Teller relaxation model up to 6, 000 K and a steady-state approach above 6, 000 K. Temperature sweep measurements were fixed around 223.237 nm, while wavelength sweep measurements were taken around 4550 K and ranged between 223.23 nm to 223.27 nm. Temperature sweep cross-sections agree to within 15% of Specair modeled cross-sections, with most measurements falling within 10% of Specair predictions. Wavelength sweep cross-sections agree at shorter wavelengths with Specair cross-sections, but longer wavelength features are offset from both the Stanford model and Specair predictions. Changing the spin-splitting equations used by the Stanford model from the Herzberg formulation to the Nicolet formulation also brought the Stanford model to within 15% of all temperature sweep data, with most measurements falling within 10% of the Stanford model predicts. The spin-splitting adjustment also improved the agreement between the Stanford model and the wavelength sweep data at shorter wavelengths.